Collaborative Writing Learning in Inquiry to Improve Critical Thinking Skills - Shofiah, Nurul; Putera, Zulmy Faqihuddin; Widiastuti, Sripit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
In tertiary education, the enhancement of writing skills is paramount. One effective approach to mastering academic writing is through inquiry-based collaborative learning. Hence, this study endeavors to delineate the procedures involved and gauge students' perceptions of inquiry-based collaborative writing in enhancing critical thinking skills within the Indonesian language curriculum. This research adopts a descriptive methodology, employing research instruments such as observation sheets and surveys to gather data. The findings elucidate two key points: firstly, the inquiry-based collaborative writing process comprises five integral stages - orientation, collaboration, investigation, discussion, and conclusion. Secondly, student feedback highlights the positive impact of this method in nurturing critical thinking skills specifically within the realm of Indonesian language studies. Given its fusion of activity-oriented learning, logical argumentation, and collaborative dynamics, inquiry-based collaborative writing emerges as a potent tool for cultivating critical thinking skills among students. Consequently, its incorporation into the curriculum is recommended as a strategic means to bolster students' cognitive abilities and academic proficiency